Postgraduate Internationalisation in Brazil (International Journal of Scientific Research and Management (IJSRM), 2021)
Understanding the current state of the Internationalisation of postgraduate courses in Brazil was essential to serve as a basis for constructing effective policies in funding agencies. It also helps to understand the capacity of the higher education institution to carry out more effective strategic planning and internationalisation plans. This study looks at replies to a Brazilian national funding agency (CAPES) questionnaire on Internationalisation within Higher Education Institutes in Brazil, based on the postgraduate experience. Results showed that Internationalisation is based on mobility with little comprehensive thinking on its role towards academic achievement within the Postgraduate Programs realities, beyond the mobile individual. English language skills need to be improved. While most institutions have offices that treat this theme, they lack an active engagement with the postgraduate programs and strategic planning, seen as vital for almost all institutions. Resources are necessary to build infrastructure and capacitate lecturers and staff to this end.